2019
DOI: 10.15835/nbha47411348
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Salt and Water Stress Tolerance in Fir (Abies alba) Populations

Abstract: Drought periods are becoming more frequent and intense, due to the effects of climate change, threatening natural habitats worldwide, including European forests. Forest trees can also be affected by high soil salinity, because of the common practice of de-icing of mountain roads with NaCl in winter. We have evaluated the responses to salt and water stress of silver fir (Abies alba), an important forest species for which very limited information is available. One-year-old fir seedlings, with origin in seven dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…We found that moderate water deprivation mediated drought hardening in both species and that this effect was partially counteracted by rewatering. Similar results were not obtained in previous studies with beech or fir seedlings in monocultures [24,[27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 89%
“…We found that moderate water deprivation mediated drought hardening in both species and that this effect was partially counteracted by rewatering. Similar results were not obtained in previous studies with beech or fir seedlings in monocultures [24,[27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 89%
“…In most plant species, therefore, determination of growth parameters is commonly used to assess the effects of stress on the plants. This approach is not so useful for slow-growing species such as conifers, including the silver fir, especially in the first years of life [22,57,58]. Nevertheless, after one month of water and salt stress treatments, we could detect a significant inhibition of growth in one-year-old silver fir seedlings, indicating that at this developmental stage, this species is relatively more sensitive to drought and high salinity than other conifers, for example, Picea abies [59].…”
Section: Effect Of Salt and Water Stress On Seedlings' Growth And Phomentioning
confidence: 93%
“…This observation aligns with prior research indicating pronounced differentiation in silver fir populations concerning growth, ecophysiological, and biochemical traits. Such distinctions are attributed to disjunctions in its distribution, as indicated by the effects of the applied stress, as demonstrated in earlier studies with other stress factors (Șchiop et al, 2015;Todea et al, 2019).…”
Section: Discussion Discussion Discussionmentioning
confidence: 64%
“…is one of the most important forest trees in Central Europe, particularly in mountainous terrain and in the continent's southern and eastern regions (Ancuceanu et al, 2023). It is acknowledged as a valuable forest species due to its numerous uses (Todea et al, 2019;Todea et al, 2020).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%